Watering the Revolution : An Environmental and Technological History of Agrarian Reform in Mexico - Wolfe, Mikael (Book collections on Project MUSE., 2017)
Mikael D. Wolfe transforms our understanding of Mexican agrarian reform through an environmental and technological history of water management in the emblematic Laguna region. Drawing on extensive archival research in Mexico and the United States, Wolfe shows how during the long Mexican Revolution (1910-1940) engineers' distribution of the water paradoxically undermined land distribution. In so doing, he highlights the intrinsic tension engineers faced between the urgent need for water conservation and the imperative for development during the contentious modernization of the Laguna's existing flood irrigation method into one regulated by high dams, concrete-lined canals, and motorized groundwater pumps. This tension generally resolved in favor of development, which unintentionally diminished and contaminated the water supply while deepening existing rural social inequalities by dividing people into water haves and have-nots, regardless of their access to land. By uncovering the varied motivations behind the Mexican government's decision to use invasive and damaging technologies despite knowing they were ecologically unsustainable, Wolfe tells a cautionary tale of the long-term consequences of short-sighted development policies.